Contribution due to clumpy winds to the non-thermal emission in microquasar jets - de la Cita, M. V. (2017)
Powerful jets in high-mass microquasars are likely to be crossed by dense inhomogeneities(clumps) from the stellar winds, which may lead to particle acceleration and thus nonthermalemission in X-rays and gamma-rays. We characterise a typical clump-jet interactionscenario and compute the contribution to the high-energy emission of these systems. Weuse hydrodynamical simulations of a single clump-jet interaction and we use this result tocompute its non-thermal (synchrotron and inverse Compton) radiation. We present severalradiative calculations for a number of clump states, as the clump is disrupted over time,letting different parameters vary (viewing angle, magnetic field). We obtain significantamounts of non-thermal radiation from jet-clump interactions in high-mass microquasars.